Carbon deposition prevention catalyst, preparation method and application
Patent Information
- Application Number
- JP2024548666
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-04
- Filing Date
- 2023-03-03
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-03-03
Smart Images

Figure 2025505302000001 
Figure 2025505302000002 
Figure 2025505302000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of catalysis, in particular to an anti-carbon deposition catalyst, its preparation method and application. [Background technology]
[0002] Chlorotrifluoroethylene is a colorless gas with a slight ethereal odor. It has excellent reactivity and is an important fluorine-containing polymerization monomer. It is also an important chemical intermediate and is widely used in fields such as pesticides, medicine, and polymer materials.
[0003] Chinese patent application CN1110103604A discloses a catalyst for catalytic hydrodechlorination, its preparation method and application, in which the alloy catalyst is mainly made of element Ru, and one or more of the specified alloy elements Re, Ti, Cr, Ni, Al, Co, Cu, Nb, Ta, Ru, Pt or Ag are selected to form an alloy with Ru, the auxiliary is an alkali metal or alkaline earth metal, and the carrier is an activated carbon carrier.When it is used to prepare chlorotrifluoroethylene, the conversion rate of chlorotrifluoroethylene is about 95.7%, and the selectivity is 95.6%.
[0004] However, the synthesis of CTFE by catalytic hydrogenation has an important core problem: how to suppress carbon deposition. The presence of carbon deposition does not affect the raw material conversion rate or product selectivity at the beginning of the reaction, but it has a significant impact on the stability and life of the catalyst. Existing literature reports that carbon deposition is mainly affected by the acidity of the catalytic active sites and the reaction temperature. Therefore, reducing the acidity of the active sites or increasing the catalytic activity (reducing the reaction temperature) can effectively suppress carbon deposition and extend the life of the catalyst.
[0005] Chinese patent application CN1589970A discloses a method for regenerating a catalyst for producing alkenyl aromatics by dehydrogenating alkyl aromatic hydrocarbons, in which steam and air are used to regenerate the catalyst through a hydrothermal method, but a higher regeneration temperature is required to completely burn off the carbon adhering to the catalyst.
[0006] Chinese patent application CN107497420A discloses a method for regenerating carbon-containing precious metal catalysts, in which the oxygen content in the regeneration gas is controlled stepwise during the combustion process, the carbon deposited on the catalyst is removed by stepwise combustion, and the activity of the catalyst is restored by chlorination and reduction. In the regeneration process of precious metal catalysts, if the moisture content is too high during the chlorination operation, the activity of the catalyst will decrease, so the method requires strict control of the moisture in the process gas and the maximum operating temperature to ensure the regeneration efficiency.
[0007] Chinese patent application CN107999057A discloses a method for regenerating supported precious metal catalyst, in which the deactivated supported precious metal catalyst is oxidized with a mixture of CO2 and O2, and then reduced with a reducing agent in tetrahydrofuran solvent to obtain a regenerated catalyst.
[0008] In short, the occurrence of carbon deposits cannot be completely suppressed in the conventional catalysts and their catalytic hydrogenation processes, and the carbon deposits can only be removed by regenerating the carbon deposits after their occurrence, that is, by using air, CO2, H2O and other gases to chemically react with the carbon deposits to remove them. However, the process of removing the carbon deposits inevitably damages the carrier carbon, destroys the structure of the catalyst particles, and causes irrecoverable catalyst deactivation. Therefore, it is difficult to control the process of removing the carbon deposits.
[0009] So far, there are no related reports that effectively solve the problem of carbon deposition in catalytic hydrodechlorination catalysts. Summary of the Invention
[0010] The object of the present invention is to provide a fluorochloroalkane hydrodechlorination catalyst which can effectively prevent carbon deposition, and its preparation method and application.
[0011] According to one aspect of the present invention, the present invention uses the following technical solutions:
[0012] A carbon deposition prevention catalyst, which is composed of a carbon support, a metal active component, a metal auxiliary I and a metal auxiliary II, the metal active component is platinum or palladium, the metal auxiliary I is zinc, copper or cobalt, the metal auxiliary II is ruthenium or nickel, and each type of metal component has only one type of metal.
[0013] The mass content of the metal active component in the carrier is 0.2-2.0%, and the mass ratio of the metal active component, metal auxiliary I, and metal auxiliary II is 1:(1-10):(0.01-0.001).
[0014] Preferably, the mass content of the metal active component in the carrier is 0.2 to 1.5%.
[0015] Preferably, the mass ratio of the metal active component, the metal auxiliary I and the metal auxiliary II is 1:(1-8):(0.01-0.003).
[0016] The carbon carrier is activated carbon, preferably in granular form, and has an ash content of 2% by weight or less.
[0017] According to a second aspect of the present invention, the present invention further provides a method for preparing a carbon deposition prevention catalyst, specifically comprising the following steps:
[0018] A1. Activated carbon treatment step Using a sodium hydroxide solution with a molar concentration of 1 to 5 mol / L, the activated carbon is immersed and washed at 50 to 90°C for 2 to 6 hours, and then washed with water until it becomes neutral. Using hydrochloric acid with a molar concentration of 0.5 to 3 mol / L, the activated carbon is immersed and washed at 20 to 60°C for 2 to 6 hours, and then washed with water until it becomes neutral. The ratio of activated carbon to sodium hydroxide solution / hydrochloric acid is 1:1.5 to 3.0 (g / mL), and g / mL represents the immersion and washing of 1 g of activated carbon in 1 mL of sodium hydroxide solution / hydrochloric acid.
[0019] The purpose of this step is to remove the metallic ash in the activated carbon so that the content of individual metal components is 0.01% by weight or less.
[0020] A2. Preparation of immersion solution Weigh out the metal active ingredient salt, the metal auxiliary I salt and the metal auxiliary II salt, and mix them uniformly in the aqueous solution of ammonium citrate and glycolic acid to form an immersion solution;
[0021] The above-mentioned metal active component salt, metal auxiliary I salt and metal auxiliary II salt are all soluble salts.Specifically, the metal active component salt can be platinum or palladium chloride or nitrate, such as platinum dichloride, platinum tetrachloride and palladium dichloride, and the metal auxiliary I salt can be a soluble salt of zinc, copper or cobalt selected from chloride salts, nitrates, sulfates or organic salts, such as zinc chloride, copper chloride, cobalt chloride, copper nitrate, cobalt nitrate, zinc sulfate, copper sulfate, cobalt sulfate, zinc acetate, cobalt acetate, etc.The metal auxiliary II salt can be a soluble salt of ruthenium or nickel, such as hydrated ruthenium trichloride, ruthenium acetate, nickel chloride, nickel nitrate, nickel sulfate, nickel acetate, etc.
[0022] A3. Activated carbon immersion The activated carbon treated in step A1 is added to the soaking solution in step A2, stirred at 20-50°C for 2-5 hours, and then left to stand for 5-12 hours to mature, after which the activated carbon is taken out and dried, the drying can be air-dried or oven-dried, the volume of the soaking solution is 1.5-2 times the pore volume of the activated carbon, and isovolume soaking, and the pore volume of the activated carbon is measured by the BET method;
[0023] A4. Catalyst synthesis steps The activated carbon carrying the metal component is roasted in an inert atmosphere, the temperature is raised from room temperature to 200-600°C at a rate of 1-5°C / min, and the temperature is kept constant for 2-5 hours to obtain a carbon deposition prevention catalyst. Specifically, the inert gas is nitrogen or argon gas, and the flow rate is 1-10 mL / min.
[0024] Roasting not only roasts the metal salt to form an oxide, but also strengthens the bonding strength between each metal component and between each metal component and the activated carbon carrier, thereby improving the stability of the catalyst.
[0025] Furthermore, the molar ratio of ammonium citrate to glycolic acid is 1:1 to 3, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metals is 1:1 to 3. Preferably, the molar ratio of ammonium citrate to glycolic acid is 1:1.5 to 2.5, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metals is 1:1.5 to 2.5.
[0026] According to a third aspect of the present invention, the present invention further provides an application of the carbon deposition prevention catalyst prepared as above, specifically, the carbon deposition prevention catalyst is used for hydrodechlorination reaction, more specifically, the carbon deposition prevention catalyst is used for the preparation of chlorotrifluoroethylene by hydrodechlorination of trifluorotrichloroethane, the preparation of ethylene by hydrodechlorination of 1,1,2-trichloroethylene, the preparation of pentafluoroethane by hydrodechlorination of pentafluorochloroethane, the preparation of 1-chloro-tetrafluoroethane and tetrafluoroethane by hydrodechlorination of 1,1-dichlorotetrafluoroethane, and the preparation of 1,1,1,4,4,4-hexafluoro-2-butene by hydrodechlorination of 2,3-dichloro-1,1,1,4,4,4-hexafluoro-2-butene.
[0027] When the carbon deposition prevention catalyst according to the present invention is used for hydrodechlorination, the carbon deposition prevention catalyst is reduced and activated before the raw material gas is supplied to carry out the hydrodechlorination reaction, and the reduction and activation step includes the following steps:
[0028] The carbon deposition prevention catalyst is placed in a reactor and activated by reducing it with hydrogen. The volumetric space velocity of hydrogen is 2 to 8 min -1 The heating program is 1-3°C / min, and includes heating from room temperature to 300-400°C and maintaining the temperature constant for 1-3 hours.
[0029] Furthermore, the ratio of catalyst particle size to reactor inner diameter is 1:(6-10).
[0030] Furthermore, in the present application, ammonia gas and raw material gas are simultaneously supplied to a reactor to carry out a hydrodechlorination reaction, so that the content of ammonia gas and the amount of hydrogen chloride produced are equal, and the molar ratio of the two is set to 1:1.
[0031] The present invention further provides a method for preparing chlorotrifluoroethylene by hydrodechlorination of trifluorotrichloroethane, specifically including:
[0032] Ammonia gas, trifluorotrichloroethane (R113) and hydrogen are simultaneously fed into a tubular reactor to carry out a hydrodechlorination reaction. The reaction temperature is 250-350°C, and the space velocity of trifluorotrichloroethane is 40-100 h -1 The molar ratio of R113 to hydrogen is 1:(1 to 3), preferably 1:(1.5 to 2.5), and the ratio of the ammonia gas content to the generated hydrogen chloride is set to 1:1.
[0033] In the actual reaction, the ammonia gas flow rate is initially set according to the theoretical hydrogen chloride content obtained by the reaction of R113 with hydrogen, and the hydrogen chloride content in the product stream is monitored during the reaction process to adjust the ammonia gas flow rate.
[0034] Compared with the prior art, the advantages of the present invention are mainly reflected in the following:
[0035] 1) The three kinds of metal auxiliaries in the carbon deposition prevention catalyst of the present invention can form a multifunctional catalytic activity center, which can achieve in-situ hydrogenation removal of carbon deposits while maintaining high dechlorination catalytic performance, without causing macroscopic carbon deposition, effectively inhibit the occurrence of carbon deposition, and improve the stability and life of the catalyst.
[0036] 2) When the carbon deposition prevention catalyst of the present invention is used in hydrodechlorination, alkaline ammonia gas is supplied simultaneously with the raw gas to reduce the acidity of the active center, inhibit the adsorption of acidic hydrogen chloride and adsorbed chlorine on the catalyst surface, and reduce the occurrence of carbon deposition. At the same time, an appropriate amount of ammonia gas can also react with hydrogen chloride to promote the dechlorination reaction to the right and increase the conversion rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The embodiments of the present invention will be described in more detail below with reference to specific examples, but the scope of protection of the present invention is not limited to the following examples.
[0038] The metal active ingredient salt, metal auxiliary I salt, metal auxiliary II salt, sodium hydroxide, hydrochloric acid, ammonium citrate and glycolic acid used in the examples were all obtained from Sinopharm Chemical Reagent Co., Ltd., and the activated carbon was obtained from Aladdin Chemical Purchasing Management Platform. The specific surface area of the activated carbon was 1100 m 2 / g, pore volume 0.7648cc / g, and ash content 1.5 wt%.
[0039] Example 1 (1) Weigh out 8.0 mg of PtCl2, 8.0 mg of Cu(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:1, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2. Then, add deionized water to prepare an immersion solution with a total volume of 5.0 mL, and stir at 50°C for 5 hours.
[0040] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 6 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 2 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 6 mL of 0.5 mol / L hydrochloric acid and stirred at 20°C for 2 hours. After that, the activated carbon is washed with deionized water until it becomes neutral, and then air-dried to obtain a treated activated carbon carrier.
[0041] (3) Place the treated activated carbon granular carrier in the soaking solution prepared in step (1), gently stir the soaking solution, and leave it overnight after soaking is complete. After drying in a nitrogen atmosphere with a nitrogen flow rate of 1 mL / min, heat from room temperature to 220°C at a rate of 1°C / min and keep the temperature constant for 2 hours to obtain a carbon precipitated catalyst.
[0042] (4) The catalyst prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:6, hydrogen is supplied to activate it by reduction, and the volumetric space velocity of hydrogen is 2 min -1 Then, the temperature is increased from room temperature to 300°C at a rate of 1°C / min and kept constant for 3 hours.
[0043] (5) After reduction and activation are completed, the volumetric space velocity of hydrogen is increased to 2 min. -1 The gasified trifluorotrichloroethane (R113) was supplied, and the volumetric space velocity of R113 was maintained at 40 h. -1 At the same time, ammonia gas was supplied at a flow rate of 1.4 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 250°C.
[0044] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.45%, and the selectivity of chlorotrifluoroethylene is 96.78%.
[0045] Example 2 (1) Weigh out 8.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid such that the molar ratio of ammonium citrate to glycolic acid is 1:2, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:1. Then, add deionized water to prepare an immersion solution with a total volume of 6.0 mL, and stir at 20°C for 2 hours.
[0046] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 6 mL of 3 mol / L sodium hydroxide solution and stirred at 70°C for 4 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 6 mL of 1 mol / L hydrochloric acid and stirred at 40°C for 4 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0047] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 3 mL / min, the temperature is raised from room temperature to 200°C at a rate of 3°C / min, and the temperature is kept constant for 3 hours to obtain a carbon precipitate catalyst.
[0048] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:10. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 8 min -1 Then, the temperature is increased from room temperature to 400° C. at a rate of 3° C. / min, and the temperature is kept constant for 3 hours.
[0049] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 8 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 100 h. -1 At the same time, ammonia gas was supplied at a flow rate of 3.4 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 350°C.
[0050] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.95%, and the selectivity for chlorotrifluoroethylene is 96.89%.
[0051] Example 3 (1) Weigh out 8.0 mg of PtCl2, 40.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:3, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:3. Then, add deionized water to prepare an immersion solution with a total volume of 6.5 mL, and stir at 30°C for 3 hours.
[0052] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 8 mL of 5 mol / L sodium hydroxide solution and stirred at 90°C for 6 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 6 mL of 3 mol / L hydrochloric acid and stirred at 60°C for 6 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0053] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 5 mL / min, the temperature is raised from room temperature to 200°C at a rate of 5°C / min, and the temperature is kept constant for 4 hours to obtain a carbon precipitated catalyst.
[0054] (4) The catalyst prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:8, hydrogen is supplied to activate it by reduction, and the space velocity of hydrogen is 6 min -1 Then, the temperature is increased from room temperature to 350° C. at a rate of 2° C. / min and kept constant for 2 hours.
[0055] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 6 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 60 h.-1 At the same time, ammonia gas was supplied at a flow rate of 2.1 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 280°C.
[0056] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 97.23%, and the selectivity for chlorotrifluoroethylene is 97.18%.
[0057] Example 4 (1) Weigh out 12.0 mg of PtCl2, 80.0 mg of Co(NO3)2, and 0.012 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:3, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2. Then, add deionized water to prepare an immersion solution with a total volume of 7.0 mL, and stir at 50°C for 2 hours.
[0058] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 6 mL of 4 mol / L sodium hydroxide solution and stirred at 80°C for 5 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 8 mL of 1 mol / L hydrochloric acid and stirred at 50°C for 3 hours. After that, the activated carbon is washed with deionized water until it becomes neutral, and then air-dried to obtain a treated activated carbon carrier.
[0059] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 7 mL / min, the temperature is raised from room temperature to 250°C at a rate of 5°C / min, and the temperature is kept constant for 5 hours to obtain a carbon precipitated catalyst.
[0060] (4) The catalyst thus prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:9, hydrogen is supplied to activate it by reduction, and the space velocity of hydrogen is 8 min -1Then, the temperature is increased from room temperature to 320° C. at a rate of 2° C. / min and kept constant for 2 hours.
[0061] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 8 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 80 h. -1 At the same time, ammonia gas was supplied at a flow rate of 2.7 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 300°C.
[0062] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 97.65%, and the selectivity for chlorotrifluoroethylene is 97.09%.
[0063] Example 5 (1) Weigh out 16.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.012 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:2, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:3. Then, add deionized water to prepare an immersion solution with a total volume of 6.0 mL, and stir at 20°C for 5 hours.
[0064] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 9 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 2 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 9 mL of 0.5 mol / L hydrochloric acid and stirred at 30°C for 3 hours. After that, the activated carbon is washed with deionized water until it becomes neutral, and then air-dried to obtain a treated activated carbon carrier.
[0065] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 10 mL / min, the temperature is raised from room temperature to 250°C at a rate of 5°C / min, and the temperature is kept constant for 5 hours to obtain a carbon precipitated catalyst.
[0066] (4) The catalyst prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:7, hydrogen is supplied to activate it by reduction, and the space velocity of hydrogen is 4 min -1 Then, the temperature is increased from room temperature to 400°C at a rate of 1°C / min and kept constant for 1 hour.
[0067] (5) After reduction and activation are completed, the hydrogen space velocity is increased to 4 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 70 h. -1 At the same time, ammonia gas was supplied at a flow rate of 2.4 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 350°C.
[0068] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 95.22%, and the selectivity for chlorotrifluoroethylene is 97.82%.
[0069] Example 6 (1) Weigh out 8.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid such that the molar ratio of ammonium citrate to glycolic acid is 1:1, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:1. Then, add deionized water to prepare an immersion solution with a total volume of 7.0 mL, and stir at 50°C for 3 hours.
[0070] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 9 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 4 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 6 mL of 0.5 mol / L hydrochloric acid and stirred at 50°C for 4 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0071] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 10 mL / min, the temperature is raised from room temperature to 220°C at a rate of 3°C / min, and the temperature is kept constant for 5 hours to obtain a carbon precipitate catalyst.
[0072] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:10. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 5 min -1 Then, the temperature is increased from room temperature to 400° C. at a rate of 3° C. / min, and the temperature is kept constant for 3 hours.
[0073] (5) After reduction and activation are completed, the hydrogen space velocity is increased to 5 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 100 h. -1 At the same time, ammonia gas was supplied at a flow rate of 3.4 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 330°C.
[0074] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.65%, and the selectivity for chlorotrifluoroethylene is 96.21%.
[0075] Example 7 (1) Weigh out 8.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:3, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:1. Then, add deionized water to prepare an immersion solution with a total volume of 5.5 mL, and stir at 30°C for 2 hours.
[0076] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 6 mL of 3 mol / L sodium hydroxide solution and stirred at 80°C for 6 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 6 mL of 3 mol / L hydrochloric acid and stirred at 50°C for 4 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0077] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 1 mL / min, the temperature is raised from room temperature to 200°C at a rate of 1°C / min, and the temperature is kept constant for 2 hours to obtain a carbon precipitate catalyst.
[0078] (4) The catalyst thus prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:9, hydrogen is supplied to activate it by reduction, and the space velocity of hydrogen is 8 min -1 Then, the temperature is increased from room temperature to 300° C. at a rate of 3° C. / min, and the temperature is kept constant for 1 hour.
[0079] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 8 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 90 h. -1 At the same time, ammonia gas was supplied at a flow rate of 3.1 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 330°C.
[0080] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.45%, and the selectivity for chlorotrifluoroethylene is 97.34%.
[0081] Example 8 (1) Weigh out 8.0 mg of PdCl2, 80.0 mg of Cu(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:2, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:1. Then, add deionized water to prepare an immersion solution with a total volume of 6.0 mL, and stir at 30°C for 5 hours.
[0082] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 10 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 2 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 10 mL of 0.5 mol / L hydrochloric acid and stirred at 20°C for 2 hours. After that, the activated carbon is washed with deionized water until it becomes neutral, and then air-dried to obtain a treated activated carbon carrier.
[0083] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 10 mL / min, the temperature is raised from room temperature to 250°C at a rate of 1°C / min, and the temperature is kept constant for 3 hours to obtain a carbon precipitate catalyst.
[0084] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:8. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 8 min -1 Then, the temperature is increased from room temperature to 380° C. at a rate of 1° C. / min, and the temperature is kept constant for 3 hours.
[0085] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 8 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 60 h.-1 At the same time, ammonia gas was supplied at a flow rate of 2.1 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 350°C.
[0086] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 98.75%, and the selectivity for chlorotrifluoroethylene is 95.87%.
[0087] Example 9 (1) Weigh out 8.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:2, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2. Then, add deionized water to prepare an immersion solution with a total volume of 7.0 mL, and stir at 30°C for 3 hours.
[0088] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 12 mL of 1 mol / L sodium hydroxide solution and stirred at 60°C for 4 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 6 mL of 0.5 mol / L hydrochloric acid and stirred at 30°C for 4 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0089] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 10 mL / min, the temperature is raised from room temperature to 250°C at a rate of 1°C / min, and the temperature is kept constant for 5 hours to obtain a carbon precipitate catalyst.
[0090] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:10. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 8 min -1Then, the temperature is increased from room temperature to 400° C. at a rate of 2° C. / min, and the temperature is kept constant for 3 hours.
[0091] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 8 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 100 h. -1 At the same time, ammonia gas was supplied at a flow rate of 3.4 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 340°C.
[0092] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.35%, and the selectivity for chlorotrifluoroethylene is 96.77%.
[0093] Example 10 (1) Weigh out 8.0 mg of PtCl2, 80.0 mg of Cu(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:3, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2.5. Then, add deionized water to prepare an immersion solution with a total volume of 5.5 mL, and stir at 50°C for 5 hours.
[0094] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 12 mL of 1 mol / L sodium hydroxide solution and stirred at 90°C for 6 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 12 mL of 3 mol / L hydrochloric acid and stirred at 60°C for 6 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0095] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 8 mL / min, the temperature is raised from room temperature to 250°C at a rate of 4°C / min, and the temperature is kept constant for 3 hours to obtain a carbon precipitated catalyst.
[0096] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:10. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 5 min -1 Then, the temperature is increased from room temperature to 370° C. at a rate of 3° C. / min, and the temperature is kept constant for 2 hours.
[0097] (5) After reduction and activation are completed, the hydrogen space velocity is increased to 5 min. -1 The gasified trifluorotrichloroethane (R113) was supplied, and the volumetric space velocity of R113 was maintained at 80 h. -1 At the same time, ammonia gas was supplied at a flow rate of 2.7 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 270°C.
[0098] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 97.85%, and the selectivity of chlorotrifluoroethylene is 95.86%.
[0099] Example 11 (1) Weigh out 8.0 mg of PdCl2, 80.0 mg of Zn(NO3)2, and 0.08 mg of ruthenium chloride, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:1.5, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:3. Then, add deionized water to prepare an immersion solution with a total volume of 6.0 mL, and stir at 50°C for 5 hours.
[0100] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 10 mL of 5 mol / L sodium hydroxide solution and stirred at 80°C for 3 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 12 mL of 2 mol / L hydrochloric acid and stirred at 50°C for 2 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0101] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 5 mL / min, the temperature is raised from room temperature to 250°C at a rate of 3°C / min, and the temperature is kept constant for 3 hours to obtain a carbon precipitated catalyst.
[0102] (4) The catalyst prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:7, hydrogen is supplied to activate it by reduction, and the space velocity of hydrogen is 4 min -1 Then, the temperature is increased from room temperature to 340° C. at a rate of 2° C. / min and kept constant for 2 hours.
[0103] (5) After reduction and activation are completed, the hydrogen space velocity is increased to 4 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 90 h. -1 At the same time, ammonia gas was supplied at a flow rate of 3.1 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 260°C.
[0104] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 97.15%, and the selectivity for chlorotrifluoroethylene is 96.45%.
[0105] Example 12 (1) Weigh out 8.0 mg of PdCl2, 80.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:2, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2.5. Then, add deionized water to prepare an immersion solution with a total volume of 5.5 mL, and stir at 50°C for 5 hours.
[0106] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 10 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 5 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 12 mL of 0.5 mol / L hydrochloric acid and stirred at 20°C for 6 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0107] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 10 mL / min, the temperature is raised from room temperature to 230°C at a rate of 5°C / min, and the temperature is kept constant for 4 hours to obtain a carbon precipitate catalyst.
[0108] (4) The catalyst thus prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:7, hydrogen is supplied to activate it by reduction, and the space velocity of hydrogen is 6 min -1 Then, the temperature is increased from room temperature to 330° C. at a rate of 3° C. / min, and the temperature is kept constant for 1 hour.
[0109] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 6 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 100 h. -1 At the same time, ammonia gas was supplied at a flow rate of 3.4 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 300°C.
[0110] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 97.05%, and the selectivity for chlorotrifluoroethylene is 97.09%.
[0111] (Example 13) (1) Weigh out 8.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:3, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2. Then, add deionized water to prepare an immersion solution with a total volume of 6.0 mL, and stir at 50°C for 5 hours.
[0112] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 9 mL of 1 mol / L sodium hydroxide solution and stirred at 90°C for 2 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 9 mL of 0.5 mol / L hydrochloric acid and stirred at 60°C for 2 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0113] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 10 mL / min, the temperature is raised from room temperature to 250°C at a rate of 1°C / min, and the temperature is kept constant for 5 hours to obtain a carbon precipitate catalyst.
[0114] (4) The catalyst thus prepared is placed in a tubular reactor, the ratio of catalyst particle size to reactor inner diameter is 1:7, hydrogen is supplied to activate it by reduction, and the space velocity of hydrogen is 5 min -1 Then, the temperature is increased from room temperature to 400°C at a rate of 1°C / min and kept constant for 3 hours.
[0115] (5) After reduction and activation are completed, the hydrogen space velocity is increased to 5 min. -1 The gasified R113 was fed and the space velocity of R113 was maintained at 60 h.-1 At the same time, ammonia gas was supplied at a flow rate of 2.1 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 320°C.
[0116] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 97.93%, and the selectivity of chlorotrifluoroethylene is 96.59%.
[0117] Example 14 (1) Weigh out 8.0 mg of PtCl2, 80.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:3, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2.5. Then, add deionized water to prepare an immersion solution with a total volume of 5.0 mL, and stir at 50°C for 5 hours.
[0118] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 7 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 5 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 8 mL of 0.5 mol / L hydrochloric acid and stirred at 20°C for 5 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0119] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 8 mL / min, the temperature is raised from room temperature to 250°C at a rate of 5°C / min, and the temperature is kept constant for 2 hours to obtain a carbon precipitated catalyst.
[0120] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:10. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 6 min -1Then, the temperature is increased from room temperature to 320° C. at a rate of 1° C. / min, and the temperature is kept constant for 3 hours.
[0121] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 6 min. -1 The gasified raw gas was supplied and the space velocity of the raw gas was maintained at 50 h. -1 At the same time, ammonia gas was supplied at a flow rate of 1.7 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 260°C.
[0122] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.90%, and the selectivity for chlorotrifluoroethylene is 96.69%.
[0123] Example 15 (1) Weigh out 8.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:1, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:2. Then, add deionized water to prepare an immersion solution with a total volume of 6.5 mL, and stir at 50°C for 5 hours.
[0124] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 6 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 2 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 9 mL of 3 mol / L hydrochloric acid and stirred at 20°C for 5 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0125] (3) The activated carbon granular carrier treated in step (2) is placed in the soaking solution prepared in step (1), the soaking solution is gently stirred, and after soaking is completed, it is left to stand overnight. After drying in a nitrogen atmosphere with a nitrogen flow rate of 1 mL / min, the temperature is raised from room temperature to 250°C at a rate of 1°C / min, and the temperature is kept constant for 2 hours to obtain a carbon precipitated catalyst.
[0126] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:10. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 3 min -1 Then, the temperature is increased from room temperature to 380° C. at a rate of 1° C. / min, and the temperature is kept constant for 1 hour.
[0127] (5) After reduction and activation are completed, the hydrogen space velocity is increased to 3 min. -1 The gasified raw gas was supplied and the space velocity of the raw gas was maintained at 50 h. -1 At the same time, ammonia gas was supplied at a flow rate of 2.7 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 310°C.
[0128] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.65%, and the selectivity of chlorotrifluoroethylene is 96.45%.
[0129] (Example 16) (1) Weigh out 8.0 mg of PtCl2, 16.0 mg of Co(NO3)2, and 0.08 mg of nickel nitrate, and place them in a beaker containing ammonium citrate and glycolic acid, so that the molar ratio of ammonium citrate to glycolic acid is 1:2, and the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:3. Then, add deionized water to prepare an immersion solution with a total volume of 6.0 mL, and stir at 50°C for 5 hours.
[0130] (2) 4 g of 10 to 20 mesh granular activated carbon is added to a beaker containing 6 mL of 1 mol / L sodium hydroxide solution and stirred at 50°C for 6 hours. Next, the activated carbon is washed with deionized water until it becomes neutral. Thereafter, the activated carbon is added to a beaker containing 9 mL of 3 mol / L hydrochloric acid and stirred at 20°C for 5 hours. After that, the activated carbon is washed with deionized water until it becomes neutral and naturally dried to obtain a treated activated carbon carrier.
[0131] (3) The activated carbon granular carrier treated in step (2) is placed in the immersion solution prepared in step (1), the immersion solution is gently stirred, and after immersion is completed, it is left to stand overnight. After immersion in a nitrogen atmosphere with a nitrogen flow rate of 1 mL / min, the temperature is raised from room temperature to 250°C at a rate of 5°C / min, and the temperature is kept constant for 4 hours to obtain a carbon precipitate catalyst.
[0132] (4) The catalyst thus prepared is placed in a tubular reactor, and the ratio of catalyst particle size to reactor inner diameter is 1:10. Hydrogen is supplied to activate the catalyst by reduction, and the space velocity of hydrogen is 6 min -1 Then, the temperature is increased from room temperature to 400° C. at a rate of 2° C. / min and kept constant for 2 hours.
[0133] (5) After reduction and activation were completed, the hydrogen space velocity was increased to 6 min. -1 The gasified raw material gas was supplied and the space velocity of the raw material gas was maintained at 80 h. -1 At the same time, ammonia gas was supplied at a flow rate of 2.7 min. -1 which corresponds to the flow rate of hydrogen chloride produced and the reaction temperature is 330°C.
[0134] After 10 hours of stable operation, the chromatographic test shows the following area-normalized results: R113 conversion is 96.85%, and the selectivity of chlorotrifluoroethylene is 96.08%.
[0135] (Example 17) The operation of this embodiment is the same as that of Example 2, and only the reaction temperature and the space velocity of the raw gas R113 of Example 2 are changed to compare the catalytic performance under different reaction conditions. The results are shown in Table 1.
[0136] [Table 1] Note: The ratio of catalyst particle size to reactor inner diameter is 1:10, and the volumetric space velocity of hydrogen is 8 min -1 Then, the temperature is increased from room temperature to 400°C at a rate of 3°C / min and kept constant for 3 hours. After the reduction and activation are completed, the hydrogen space velocity is maintained, gasified R113 is fed, and the flow rate of ammonia gas is set to match the flow rate of hydrogen chloride produced.
[0137] (Example 18) This example tests the life experiment of Example 2, that is, performs detection analysis on the reactants under different stable operation times of Example 2, and the results are shown in Table 2.
[0138] [Table 2]
[0139] The test method is as follows: The ratio of catalyst particle size to reactor inner diameter is 1:10, and the space velocity of hydrogen is 8 min -1 Then, the temperature is increased from room temperature to 400°C at a rate of 3°C / min and kept constant for 3 hours. After reduction and activation are completed, the space velocity of hydrogen is 8 min -1 The gasified R113 was supplied, and the volumetric space velocity of R113 was maintained at 100 hours. -1 The flow rate of ammonia gas is 3.4 min -1 The reaction temperature is 350°C.
[0140] Comparative Example 1 The comparative example is compared with Example 2 to demonstrate the importance of metal active components to catalytic performance. The preparation method is the same as Example 2, the only difference is that no metal assistant II-nickel is added.
[0141] [Table 3]
[0142] The test method is as follows: The ratio of catalyst particle size to reactor inner diameter is 1:10, and the space velocity of hydrogen is 8 min -1 Then, the temperature is increased from room temperature to 400°C at a rate of 3°C / min and kept constant for 3 hours. After reduction and activation are completed, the space velocity of hydrogen is 8 min -1 The gasified R113 was supplied, and the volumetric space velocity of R113 was maintained at 100 hours. -1 The flow rate of ammonia gas is 3.4 min -1 The reaction temperature is 350°C.
[0143] Comparative Example 2 This comparative example is compared with Example 2 to demonstrate the importance of the loading form of metal active components on catalytic performance. The preparation method is the same as Example 2, the only difference is the preparation of the immersion solution, and ammonium citrate and glycolic acid are not added.
[0144] [Table 4]
[0145] Comparative Example 3 The comparative example is compared with Example 2 to demonstrate the importance of ammonia gas to catalytic performance. The preparation method is the same as Example 2, the only difference is that no ammonia gas is supplied during performance test.
[0146] [Table 5]
[0147] Comparative Example 4 This comparative example is compared with Example 2 to demonstrate the importance of metal assistant II and ammonia gas to catalytic performance. The preparation method is the same as Example 2, the only difference is that metal assistant II-nickel is not added and ammonia gas is not supplied.
[0148] [Table 6]
[0149] Comparative Example 5 This comparative example is compared with Example 2 to demonstrate the importance of the loading form of the metal active component on the catalytic performance. The preparation method is the same as Example 2, the only difference is the preparation of the immersion solution, in which only ammonium citrate is added, and no glycolic acid is added.
[0150] [Table 7]
[0151] Comparative Example 6 This comparative example is compared with Example 2 to demonstrate the importance of the loading form of the metal active component on the catalytic performance. The preparation method is the same as Example 2, the only difference is the preparation of the immersion solution, in which only glycolic acid is added, and ammonium citrate is not added.
[0152] [Table 8]
Claims
1. 1. A carbon deposition prevention catalyst, comprising: a carbon support; a metal active component; a metal auxiliary I; and a metal auxiliary II; the metal active component is platinum or palladium; the metal auxiliary I is zinc, copper, or cobalt; and the metal auxiliary II is ruthenium or nickel; each type of metal component has only one type of metal; the mass content of the metal active component in the support is 0.2-2.0%; and the mass ratio of the metal active component, the metal auxiliary I, and the metal auxiliary II is 1:(1-10):(0.01-0.001).
2. The carbon deposition prevention catalyst according to claim 1, wherein the mass content of the metal active component in the carrier is 0.2 to 1.5%.
3. The carbon deposition prevention catalyst according to claim 1 or 2, characterized in that the mass ratio of the metal active component, the metal auxiliary I and the metal auxiliary II is 1:(1-8):(0.01-0.003).
4. A method for preparing a carbon deposition prevention catalyst, the method comprising the steps of: A1. A step of performing activated carbon treatment, Using a sodium hydroxide solution having a molar concentration of 1-5 mol / L, the activated carbon is immersed and washed at 50-90°C for 2-6 hours, and then washed with water until it becomes neutral; using hydrochloric acid having a molar concentration of 0.5-3 mol / L, the activated carbon is immersed and washed at 20-60°C for 2-6 hours, and then washed with water until it becomes neutral, and the ratio of the activated carbon to the sodium hydroxide solution / hydrochloric acid is 1:1.5-5.0 (g / mL); A2. A step of preparing an immersion solution, Weighing out metal active ingredient salt, metal auxiliary I salt and metal auxiliary II salt, and uniformly mixing them in an aqueous solution of ammonium citrate and glycolic acid to form an immersion solution; A3. A step of performing activated carbon soaking, The activated carbon treated in step A1 is added to the soaking solution in step A2, stirred at 20-50°C for 2-5 hours, and then left to stand for 5-12 hours for aging, after which the activated carbon is taken out and dried, so that the volume of the soaking solution is 1.5-2 times the pore volume of the activated carbon; A4. A step of performing catalyst synthesis, and roasting the activated carbon carrying a metal component in an inert atmosphere, raising the temperature from room temperature to 200 to 600°C at a rate of 1 to 5°C / min, and maintaining the temperature constant for 2 to 5 hours to obtain a carbon deposition-preventing catalyst.
5. The method for preparing a carbon deposition prevention catalyst according to claim 4, characterized in that the molar ratio of ammonium citrate to glycolic acid is 1:1-3, the molar ratio of the sum of ammonium citrate and glycolic acid to the total metal is 1:1-3, the inert gas is nitrogen or argon, and the flow rate is 1-10 mL / min.
6. Application of the carbon deposition prevention catalyst according to any one of claims 1 to 3 in hydrodechlorination reaction, characterized in that the carbon deposition prevention catalyst is used for the preparation of chlorotrifluoroethylene by hydrodechlorination of trifluorotrichloroethane, the preparation of ethylene by hydrodechlorination of 1,1,2-trichloroethylene, the preparation of pentafluoroethane by hydrodechlorination of pentafluorochloroethane, the preparation of 1-chloro-tetrafluoroethane and tetrafluoroethane by hydrodechlorination of 1,1-dichlorotetrafluoroethane, and the preparation of 1,1,1,4,4,4-hexafluoro-2-butene by hydrodechlorination of 2,3-dichloro-1,1,1,4,4,4-hexafluoro-2-butene.
7. Before supplying a raw material gas to carry out a hydrodechlorination reaction, the carbon deposition prevention catalyst is reduced and activated, and the reduction and activation step includes: The carbon deposition prevention catalyst is placed in a reactor and activated by reducing it with hydrogen. The volumetric space velocity of hydrogen is 2 to 8 min -1 The application of the carbon deposition prevention catalyst in hydrodechlorination reaction according to claim 6, characterized in that the temperature rise program is 1-3°C / min, and includes raising the temperature from room temperature to 300-400°C and keeping the temperature constant for 1-3 hours.
8. The application of the carbon deposition prevention catalyst in hydrodechlorination reaction according to claim 7, characterized in that the ratio of catalyst particle size to reactor inner diameter is 1:(6-10).
9. The application of the carbon deposition prevention catalyst in hydrodechlorination reaction according to claim 8, characterized in that ammonia gas and raw material gas are simultaneously fed into a reactor to carry out hydrodechlorination reaction, the content of ammonia gas and the amount of hydrogen chloride produced are equal, and the molar ratio of the two is set to 1:
1.
10. A method for preparing chlorotrifluoroethylene by hydrodechlorination of trifluorotrichloroethane, comprising simultaneously supplying ammonia gas, trifluorotrichloroethane and hydrogen to a tubular reactor to carry out hydrodechlorination reaction, the reaction temperature being 250-350° C., and the space velocity of trifluorotrichloroethane being 40-100 h -1 The molar ratio of trifluorotrichloroethane to hydrogen is 1: (1-3), and the ammonia gas content and the hydrogen chloride produced are set to 1:1.
Citation Information
Patent Citations
Hydrodechlorination catalyst and application thereof in preparation of chlorotrifluoroethylene
CN105457651A
Catalyst for reducing mercaptan, preparation method and application thereof, and method for reducing mercaptan in gasoline
CN112742409A
Granular carbon-supported bimetallic catalysts modified with nitrogen and phosphorus, their preparation method and applications
JP2022549402A